Clinical And Immunological Significance Of Fibrillarin Protein In Systemic Scleroderma - Zaripov Sanjarbek (Genius Journals, 2023)
Fibrillarin antibodies have emerged as valuable serological markers with diagnostic and prognostic implications in systemic scleroderma. This review article explores the diagnostic and prognostic value of fibrillarin antibodies, highlighting their contribution to disease assessment, patient stratification, and prognosis determination. Fibrillarin antibodies can aid in the diagnosis of systemic scleroderma, particularly in cases with ambiguous clinical features, by enhancing diagnostic accuracy and facilitating early intervention. Their presence is associated with specific clinical phenotypes, including diffuse skin involvement, interstitial lung disease, pulmonary arterial hypertension, and digital ulcers. Longitudinal studies have demonstrated their potential as predictive markers for disease progression and the development of complications, such as severe organ involvement. The presence and persistence of fibrillarin antibodies have been linked to an increased risk of mortality. Careful interpretation is required, considering the occurrence of fibrillarin antibodies in other autoimmune diseases, necessitating a comprehensive evaluation of clinical, serological, and histopathological findings for accurate diagnosis. Overall, fibrillarin antibodies provide valuable insights into disease assessment, patient stratification, and prognosis determination in systemic scleroderma, with the potential to revolutionize clinical practice and improve patient outcomes. The purpose of this article is to provide a comprehensive review of the clinical and immunological significance of fibrillarin protein in systemic scleroderma. The article aims to explore the role of fibrillarin in disease pathogenesis, the prevalence and clinical associations of anti-fibrillarin antibodies, their potential impact on cellular processes and immune dysregulation, and the diagnostic and prognostic value of fibrillarin antibodies in systemic scleroderma
Keywords: Scleroderma; fibrillarin; RNA